POLUIÇÃO VISUAL NO MUNICÍPIO DE BETIM – ÊNFASE EM FAIXAS E OUTDOORS, DE ACORDO COM A LEI 5.657, DE 27 DE DEZEMBRO DE 2013 - Guimarães, Rafaela Soares Silveira; Rodrigues, Frederico Souza; Jesus, Laura Soares de; Lacerda, Mariany Aparecida Santana; Silva, Rafael Luiz Carvalho da; Pinho, Vitor Henrique Mafia Nogueira do; Lages, Cintia Garabini (Sinapse Múltipla, 2020)